Integrated green extraction method in enhancing total phenolic content and antioxidant activities of Heterotrigona itama propolis - A., Nur Diyana; M.Z., Nurin Izzati; N.Z.N., Hasnan; Koh, S.P.; Mansor, A.; Jajuli, R. (Rynnye Lyan Resources, 2023)
Propolis, a natural resinous by-product from the beehive, has captured researchers' interest due to the presence of its rich phytonutrient properties, including antioxidant, antiviral, antifungal antibacterial, and anti-inflammatory effects. With the increased awareness of environmental protection, there is a high demand for a greener alternative to extraction methods from natural sources. In the present study, several extraction methods have been tested to enhance the total phenolic content and antioxidant activities of the Heterotrigona itama propolis extract: a) thermal extraction, b) enzyme-assisted extraction, and c) combination of thermal and enzyme-assisted (TE) extraction. Total phenolic content (TPC) was determined using the Folin-Ciocalteu method, while the antioxidant activities were analysed using ferric reducing antioxidant power (FRAP) and 2,2-diphenyl-1picrylhydrazyl (DPPH) free radical scavenging assay. Generally, the TE extraction has increased the total phenolic content and antioxidant activities of propolis extract compared to the single extraction technique. The TE propolis extract showed the highest total phenolic content and DPPH free radical scavenging activities at 194.03±4.40 mg GAE/g and 90.95±1.69 mg AAE/g, respectively. Meanwhile, the thermal treatment of propolis extract obtained the highest FRAP value of 136.34±3.04 mg AAE/g. Conversely, enzymeassisted propolis extract showed the lowest total phenolic content (35.95±2.32 mg GAE/g) and antioxidant activities (FRAP value, 43.45±0.67 mg AAE/g; DPPH value, 26.73±0.94 mg AAE/g). These findings indicated that the combination of thermal and enzymeassisted (TE) technique is a highly efficient extraction method and could enhance the propolis extract's total phenolic content and antioxidant activities.